Ageing in athletics tracks: A multi-technique experimental investigation. (August 2018) - Tagliabue, Stefano; Andena, Luca; Pavan, Andrea; Marenghi, Andrea; Testa, Emanuele; Frassine, Roberto
Abstract: This is an extensive study of the ageing of athletics tracks, approached with a variety of experimental techniques. The effects of environmental variables, such as UV radiation, relative humidity, water immersion and temperature, were investigated using several artificial ageing protocols, applied to six prefabricated tracks of different color and chemical formulation. A few effective techniques capable of detecting and monitoring the changes occurring in track materials because of ageing were identified among a broad range of available experimental tests. In particular, semi-quantitative colorimetric analysis and dispersive electron spectroscopy were successfully employed to investigate surface degradation phenomena, while uniaxial compression and thermo-gravimetric analysis allowed characterization of the underlying bulk material. The combination of accelerated ageing protocols and monitoring techniques proved to be a powerful tool to study ageing in athletics tracks, with the aim of developing new products with improved durability for installations in critical areas. Highlights: Major factors concurring to ageing phenomena were identified. Degradation at the surface induced by exposure to strong UV radiation. Mechanical properties altered with increase in stiffness and loss of elasticity. Thermogravimetric analysis allows monitoring by measuring natural rubber degradation temperature.